Analysis of Food Diversification in Low-Income Communities in Korumba Village, Mandonga Sub-district, Kendari City - Putri Rahayu; Sitti Aida Adha Taridala; Hidrawati, Hidrawati (International Journal of Technology and Education Research, 2025)
This research aims to determine socio-economic and analyze the fulfillment of the food patterns of low-income people in Korumba Village. This research was carried out from May to July 2024. The subjects of this research were the people of Korumba Village, focused on people who have low income using descriptive analysis and PPH Expected Food Pattern score. The results of the first research are the socio-economic characteristics that influence food fulfillment including age with an average of 42.7, level of education with an average of 7.6, number of members with an average of 3.7, and jobs dominated by agricultural commodity traders. Secondly, the consumption patterns of low-income people living in dominated by the staple food group as a source of carbohydrates in the form of grains at 86.4%. peoples consumption patterns have also not been diversified, this can be seen from the PPH score of 55.9%, which is still far from the ideal score of 100